Micro and nanoplastics pollution Sources, distribution, uptake in plants, toxicological effects, and innovative remediation strategies for environmental sustainability - Kumar, Dharmendra (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.